1983
DOI: 10.1148/radiology.147.1.6219428
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient transluminal angioplasty.

Abstract: The treatment of 81 consecutive patients with transluminal angioplasty on an outpatient basis did not result in increased morbidity or mortality or delayed complications. The patients were treated in the emergency department observation area for four hours after angioplasty and were then allowed to slowly resume normal activities over the next 48 hours. The authors conclude that outpatient angioplasty is safe in a controlled setting and is cost effective since hospitalization is not required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…A body of literature exists on the outpatient performance of percutaneous peripheral, renal and carotid vascular procedures [6–21] as well as coronary procedures [22–31]. The majority of these reports suggest that the outpatient performance of percutaneous interventional procedures in properly selected patients is safe and well accepted by the patients themselves.…”
Section: Discussionmentioning
confidence: 99%
“…A body of literature exists on the outpatient performance of percutaneous peripheral, renal and carotid vascular procedures [6–21] as well as coronary procedures [22–31]. The majority of these reports suggest that the outpatient performance of percutaneous interventional procedures in properly selected patients is safe and well accepted by the patients themselves.…”
Section: Discussionmentioning
confidence: 99%
“…While numerous large studies regarding outpatient percutaneous coronary intervention demonstrated the safety and feasibility of this method [11][12][13], the large studies in the field of interventional radiology are less pronounced. Although different studies have attempted to demonstrate the feasibility and safety of outpatient percutaneous revascularization in patients with PAD [7,9,[14][15][16][17], the majority of studies have been focused on highly selected patients such as excluding the patients with critical limb ischemia or previous lower limb vascular surgery. However, what was revealed was that in almost every situation, complications occur during the procedure or during the 6 hours observation period, and therefore the outpatient approach will not alter the outcomes [8,9,16,18].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attempted to demonstrate the feasibility and efficacy of peripheral transluminal angioplasty (PTA) in outpatient population without compromising clinical outcomes [4][5][6][7]. Despite promising results, most of these studies are limited by relatively small cohorts, the bias of highly selected patients with no predefined protocol for outpatients and a short follow-up period.…”
Section: Ecole Doctorale Doctorat En Médecinementioning
confidence: 99%
“…Manashil et al [4] from a center in the US, in 1983 reported their experience with 81 patients that were treated as day cases. The authors included patients with occlusions up to 10 cm long that received 5000 International Units of intra-arterial heparin.…”
mentioning
confidence: 99%